Service selection approach for enhancing trustworthiness of Web service - ZHAO Sheng-hui1; WU Guo-xin1; CHEN Gui-lin3; CHEN Hai-bao3 (Tongxin xuebao)
Making use of the game theory,a model of service selection based on Nash bargaining solution was build,and an approach for enhancing Web service trustworthiness was proposed.A bargaining algorithm is designed between ser-vice sides of both complete rationality,through adjusting service price,to achieve maximum utility for both service re-questor and provider,and increase the success rate of transactions and service trustworthiness.Results of experiments show that,on the basis of the game that according to quality of service,reputation and security between service provider and requestor,the service selection can promote the establishment of trustable service computing environment and en-hance credibility of the service.